2003
DOI: 10.1126/science.1079491
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics-Driven Reaction Pathway in an Intramolecular Rearrangement

Abstract: A critical role is traditionally assigned to transition states (TSs) and minimum energy pathways, or intrinsic reaction coordinates (IRCs), in interpreting organic reactivity. Such an interpretation, however, ignores vibrational and kinetic energy effects of finite temperature. Recently it has been shown that reactions do not necessarily follow the intermediates along the IRC. We report here molecular dynamics (MD) simulations that show that dynamics effects may alter chemical reactions even more. In the heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 10 publications
3
123
0
2
Order By: Relevance
“…The 3 P states of oxygen have asymptotic degeneracies ͑5,3,1͒ corresponding to values of the total angular momentum ͑2,1,0͒, respectively. At short range these states correlate to 3 AЉ, 3 AЉ, and 3 AЈ surfaces. According to the treatment of Hoffmann and Schatz, only three of these nine are included in the four state model as only three have significant spin-orbit couplings with the one singlet state, and also correlate to ground-state products.…”
Section: A Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 P states of oxygen have asymptotic degeneracies ͑5,3,1͒ corresponding to values of the total angular momentum ͑2,1,0͒, respectively. At short range these states correlate to 3 AЉ, 3 AЉ, and 3 AЈ surfaces. According to the treatment of Hoffmann and Schatz, only three of these nine are included in the four state model as only three have significant spin-orbit couplings with the one singlet state, and also correlate to ground-state products.…”
Section: A Implementationmentioning
confidence: 99%
“…[1][2][3] Quantum tunneling becomes negligible for heavy nuclei and quantum interference is often quenched in large molecular systems at short times due to the wave-function decoherence, but nonadiabatic effects can still influence such systems. The most widely used method for including nonadiabatic effects into the dynamics of molecules is the trajectory surface hopping method ͑TSH͒, 4,5 which is based on classical evolution of trajectories that can switch between different electronic states.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, dynamics effects have been claimed to play an important role in various reactions. It appears in different ways, such as nonstatistical barrier recrossing, 3 nonstatistical product distribution, 4 shallow minimum skip on the intrinsic reaction coordinate (IRC), 5 non-IRC path, [6][7][8] and path bifurcation. 9,10 All these results suggested that the mechanism of these reactions could not be defined by the reaction paths on the PES and by the traditional TS theory.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as we make clear below, these spherical cylinders bound the true ''phase space reaction paths.'' The ability to compute these manifolds, and to track them far away from the transition region, is the key to the study of state-specific reactivity, 16,17 of dynamical effects on reactions 30,31 of control of reactivity 18,19 and as will be discussed below in more detail, of rare events.…”
Section: B the Dividing Surface The Nhim And Its Stable And Unstabmentioning
confidence: 99%